Strategi Kepala Pondok Pesantren Dalam Menciptakan Pesantren Ramah Anak di Pon. Pes. Haji Ya’qub Lirboyo Kota Kediri - M. Misbahus Surur; Nasrul Syarif; Hamam (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2026)
In essence, pesantren are known as the safest place to entrust their children, because they believe in the Islamic education system in it. In fact, the condition of the pesantren at this time is far from the word 'safe'. Acts of violence in Islamic boarding schools are one of the many acts of violence in various educational institutions. This study aims to examine the strategy of the head of the Islamic boarding school in creating a child-friendly pesantren in the Hajj Ya'qub Islamic Boarding School. This research is a qualitative research with a phenomenological approach. Informants are determined through purposive sampling techniques, data collection using observation, in-depth interviews and documentation. The results of the study are that the problems of child-friendly pesantren at the Haji Ya'qub Islamic boarding school include seniority, bullying, ignorance, fanaticism and immorality. The strategy used by the Head of the boarding school in creating a child-friendly pesantren at the Haji Ya'qub Islamic boarding school uses formulation, strategy implementation and evaluation. The results of the implementation of the Pondok Head's strategy make the pesantren safer and more comfortable, improve the quality of education and students who are more independent and characterful.